MEMPERTEGAS PERSPEKTIF PENDIDIKAN MULTIKULTURAL DALAM TRADISI ISLAM NUSANTARA DI TEMANGGUNG - Nashihin, Husna; Asih, Tri (Al Ghazali, 2019)
This field research uses the Phenomenology approach in studying the Islamic tradition of the Archipelago as a phenomenon that can be used as a basis for multicultural education. This research uses descriptive qualitative data analysis. There are seven backgrounds that make this research urgent. First, multicultural education needs to be developed in Indonesia as a nation that has a lot of diversity. Second, multicultural education developed at this time does not prioritize multicultural education based on community traditions. Third, the Islamic Archipelago tradition can be the basis of multicultural education in society. Fourth, the Nusantara Islamic Tradition in Temanggung can be used as a basis for multicultural education. Fifth, there is no such research that studies multicultural education based on Nusantara Islamic traditions in Temanggung. Next, there are five discussions which are examined in more depth. The results of this study indicate that there are 25 kinds of Nusantara Islamic traditions in Temanggung and have been studied in depth through research so that they can be used as a basis for multicultural education for people in Temanggung. The twenty five archipelago Islamic traditions include the use of the terms of prayer, tahlilan, wayang syuro month, 10 muharam grebek, interfaith nyadran, coronary corpse, tobacco season tradition, wethonan tradition, sajen tide ceremony, earth ruwat tradition, megekah nasi megono, friday pahingan, titi sedak tradition, ha ha ki ageng putih, halal bi halal interfaith, supernatural "bodo", interfaith tolerance, 7 monthly tradition, moderate yasinan, the term 'send', borehan, aboge beliefs, tradition of kupatan, seven kinds of porridge vegetables, and apeman traditions.